Enhanced detection of animal-derived microbial hazards in forested catchments using high-volume ultrafiltration and amplicon-based microbial source tracking - Lynch, Fiona; Lim, Timothy J. Y.; Steele, Mellisa; Stevens, Melita; Bata, Lamiya; Lynch, Georgia P.; Dewi, Dewa A. P. Rasmika; Sharp, Simon; Orr, Nataly; Ward, Aaron; Haydon, Shane; Tseng, Chi-Wen; et al. (Frontiers in Water, 2025)
IntroductionMonitoring of drinking water sources is an essential component of broader public health practise. However, routine water monitoring programmes that follow established methodological standards, such as low-volume grab sampling with standard filtration, have limitations in being representative. Particularly for protected source waters where (wildlife introduced) pathogens are in low concentration and are not evenly distributed. Microbial source tracking (MST) offers a promising approach to close this gap, enabling more precise identification of faecal contamination sources and their associated risk. However, as with other culture- and molecular-based approaches, the sensitivity of MST is constrained by sample capture methodology, limited by sample volume, timing, and randomness of grab sampling.MethodsThis study investigated the application of a high-volume sample concentration method (EasyElute ultrafiltration) to enhance microbial recovery from source water. All evaluation was conducted alongside standard grab sampling and filtration methods. Post-concentration analyses combined traditional culture-based quantification of faecal indicator organisms (FIOs) and reference pathogens, with 16S rRNA amplicon MST to provide an integrated approach to surveillance of animal-derived microbial risks in forested water supply catchments.ResultsThe results demonstrated that high-volume ultrafiltration enhanced bacterial recovery from source water samples, although turbidity was observed to limit overall efficiency, highlighting potential operational challenges. Comparative analysis demonstrated that amplicon-based MST produced consistent faecal source attribution across both standard and ultrafiltration methods, showing greater sensitivity at increasing volumes.DiscussionThis study advances MST methodology by demonstrating the feasibility and added sensitivity achievable through high-volume, concentrated sample collection approaches. This is particularly relevant where water samples are expected to carry low microbial loads, ultimately offering a practical approach for improving faecal source tracking and risk assessment for water sources to protect public health in water supply catchments.